2015
DOI: 10.3748/wjg.v21.i21.6518
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial radioembolization for hepatocellular carcinoma: An update and perspectives

Abstract: In the last decade trans-arterial radioembolization has given promising results in the treatment of patients with intermediate or advanced stage hepatocellular carcinoma (HCC), both in terms of disease control and tolerability profile. This technique consists of the selective intra-arterial administration of microspheres loaded with a radioactive compound (usually Yttrium90), and exerts its therapeutic effect through the radiation carried by these microspheres. A careful and meticulous selection of patients is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…Embolization of the any extrahepatic branch is conducted to avoid dispersion of microspheres to duodenum, stomach, or other nontargeted organs, and then macroaggregates of albumin labeled with technetium Tc 99 are injected. The diffusion of these particles is studied by a single photon emission computed tomography 18 (Figure 4). A single-center prospective cohort study of 291 patients treated with TARE found a complete response rate of 23% and a partial response rate of 34%.…”
Section: Radioembolizationmentioning
confidence: 99%
“…Embolization of the any extrahepatic branch is conducted to avoid dispersion of microspheres to duodenum, stomach, or other nontargeted organs, and then macroaggregates of albumin labeled with technetium Tc 99 are injected. The diffusion of these particles is studied by a single photon emission computed tomography 18 (Figure 4). A single-center prospective cohort study of 291 patients treated with TARE found a complete response rate of 23% and a partial response rate of 34%.…”
Section: Radioembolizationmentioning
confidence: 99%
“…Selective Internal Radiation Therapy (SIRT) is a form of radiotherapy that utilizes selective trans-arterial administration of radioactive yttrium90 microspheres [13]. In SIRT, radiation is the main therapeutic mechanism rather than embolization in causing of death of tumor cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…In SIRT, radiation is the main therapeutic mechanism rather than embolization in causing of death of tumor cells [13]. The first comprehensive European experience using SIR-Spheres ® for the treatment of patients with inoperable HCC reported an overallbest response rate of stable disease or partial response in 88% of patients byRECIST criteria and median overall survival was 7 months (95% CI, 2 -12 months) [14].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT, also known as TARE, or simply as radioembolization, is a form of RT delivery that utilizes selective transarterial administration of microspheres loaded with radioisotopes, like yttrium 90, iodine 121, or rhenium [62]. The short tissue penetration distance (average 2.5 mm, maximal 11 mm in Yttrium 90) which is mainly used in SIRT is ideal for brachytherapy and it avoids concomitant radiation damage to surrounding liver parenchyma.…”
Section: Sirtmentioning
confidence: 99%